The role of Treg cells in colorectal cancer and the immunotherapy targeting Treg cells - Yu, Hanqing; Yang, Ruiliang; Li, Meixiang; Li, Dan; Xu, Yuanqing (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is among the most prevalent and lethal cancers globally, accounting for approximately 10% of all cancer cases and deaths. Regulatory T (Treg) cells, which accumulate in CRC tissue, suppress anti-tumor immune responses and facilitate tumor progression. This review discusses Treg cell origins and functions, along with the mechanisms by which Tregs influence CRC development. In addition, we highlight therapeutic strategies targeting Tregs-such as immune checkpoint inhibitors and combinatorial approaches-to enhance effector T cell responses. A deeper understanding of Treg-mediated immunosuppression in CRC may inform the design of more effective immunotherapies and precision medicine strategies.